University-Industry R&D Collaboration in the United States, the United Kingdom, and Japan - Rahm, D. author. aut Link
X, 161 p.
Keywords: Over the last several decades there has been a growing interest in Research & Development (R&D) policy. This is particularly so in advanced industrialized nations that have adopted science- and technology- based strategies for national economic competitiveness. The United States, the United Kingdom, and Japan -- the three nations that are the subjects of this book -- share this policy strategy. Each of these nations is committed to hamessing the innovations that stern from scientific and technological advance to promote national economic prosperity. Governments can influence their nation's R&D efIort in three general ways. First, they can directly fund the R&D efIort through grants, loans, appropriations, or government contracts. Second, they can provide tax and financing incentives to encourage higher levels of private sector R&D. Third, they can use their power to create inter-organizational collaborations that vastly extend and expand the nation's collective R&D efIort. University-industry collaborations are a principal type of these inter organizational R&D efIorts -- and the focus of this book.